Shifting the pH profiles of Staphylococcus epidermidis lipase (SEL) and Staphylococcus hyicus lipase (SHL) through generating chimeric lipases by DNA shuffling strategy - Wan Hasan, Wan Atiqah Najiah; Nezhad, Nima Ghahremani; Yaacob, Mohd Adilin; Salleh, Abu Bakar; Raja Abdul Rahman, Raja Noor Zaliha; Leow, Thean Chor (Springer Science and Business Media, 2024)
Enzymes are often required to function in a particular reaction condition by the industrial procedure. In order to identify critical residues affecting the optimum pH of Staphylococcal lipases, chimeric lipases from homologous lipases were generated via a DNA shuffling strategy. Chimeric 1 included mutations of G166S, K212E, T243A, H271Y. Chimeric 2 consisted of substitutions of K212E, T243A, H271Y. Chimeric 3 contained substitutions of K212E, R359L. From the screening results, the pH profiles for chimeric 1 and 2 lipases were shifted from pH 7 to 6. While the pH of chimeric 3 was shifted to 8. It seems the mutation of K212E in chimeric 1 and 2 decreased the pH to 6 by changing the electrostatic potential surface. Furthermore, chimeric 3 showed 10 ˚C improvement in the optimum temperature due to the rigidification of the catalytic loop through the hydrophobic interaction network. Moreover, the substrate specificity of chimeric 1 and 2 was increased towards the longer carbon length chains due to the mutation of T243A adjacent to the lid region through increasing the flexibility of the lid. Current study illustrated that directed evolution successfully modified lipase properties including optimum pH, temperature and substrate specificity through mutations, especially near catalytic and lid regions. © The Author(s), under exclusive licence to Springer Nature B.V. 2024.